Bovine coronavirus (BCoV) and its analogy to SARS-CoV-2 – Literature review (Research, Society and Development, 2021)
Transmitted by the virus of the Coronaviridae family – and originating in group II, where the human coronavirus SARS-CoV-2 is also found – bovine coronavirus is present in diseases of the gastrointestinal tract and respiratory tract, causing neonatal diarrhea and winter dysentery in cattle adults, also associated with pneumonia. The SARS-CoV-2 coronavirus is a virus originated in China at the end of 2019, the etiologic agent of Covid-19, which mainly affects the lower respiratory tract in the population. This work aims to review the scientific literature and discuss the differences between bovine and human coronaviruses, making a comparison inherent to the prophylaxis, treatment, symptoms, diagnosis, immune system and transmission thereof, in order to clarify such peculiarities through a bibliographical review on the subject.